VOCABULARY SELF-COLLECTION STRATEGY (VSS): AN EFFORT TO IMPROVE VOCABULARY MASTERY AT THE EIGHTH GRADE STUDENTS OF SMPN 1 SUNGGUMINASA - Abdullah, Dwi Yumna; Abdullah, Muhaimin (Institut Agama Islam Negeri (IAIN) Bone, 2024)
This Classroom Action Research aims to improve students’ vocabulary mastery in the Eighth Grade of SMP Negeri 1 Sungguminasa using Vocabulary Self-collection Strategy. In this strategy, students find the meaning of difficult vocabulary that is important and interesting for them to know based on the topics that the teacher has given at the end of the previous lesson. This research was conducted in two cycles in stages consisting of planning, action, observation and reflection. The subjects of this study were 30 students in VIII-E, consisting of 13 boys and 17 girls. The results of data analysis show that the average value of vocabulary mastery in cycle I is 67 and the average value of vocabulary mastery in cycle II is 94.3. The data results showed that the learning outcomes of vocabulary mastery in cycle I to cycle II experienced an increase of 27.3. Overall, this study showed that the learning outcomes of vocabulary mastery increased using Vocabulary Self-collection Strategy of VIII-E students at SMP Negeri 1 Sungguminasa. This strategy helps students to enhance their vocabulary mastery and self-directed study habits. In addition, they showed an increased interest in writing. It is recommended that English teachers should consider Vocabulary Self-collection Strategy to improve students' vocabulary mastery.